2020
DOI: 10.1007/s41918-020-00078-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface Segregation in Solid Oxide Cell Oxygen Electrodes: Phenomena, Mitigation Strategies and Electrochemical Properties

Abstract: Solid oxide cells (SOCs) are highly efficient and environmentally benign devices that can be used to store renewable electrical energy in the form of fuels such as hydrogen in the solid oxide electrolysis cell mode and regenerate electrical power using stored fuels in the solid oxide fuel cell mode. Despite this, insufficient long-term durability over 5–10 years in terms of lifespan remains a critical issue in the development of reliable SOC technologies in which the surface segregation of cations, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 307 publications
(468 reference statements)
5
53
0
Order By: Relevance
“…The existence of Sr cluster on the LSCF surface inhibited the sites of active reaction accompanied by enlargement of R p 51 thus degrading electrochemical activities for oxygen reaction. 25 This is consistent with the findings of Rupp et al 38 as the SrO (or Sr[OH] 2 ) termination layer was reported to block the oxygen from approaching the active sites. The SrO is known as a large-band gap insulator and thus it is unlikely to enable electron transmission in ORR.…”
Section: Orr On Miec Cathodessupporting
confidence: 89%
See 3 more Smart Citations
“…The existence of Sr cluster on the LSCF surface inhibited the sites of active reaction accompanied by enlargement of R p 51 thus degrading electrochemical activities for oxygen reaction. 25 This is consistent with the findings of Rupp et al 38 as the SrO (or Sr[OH] 2 ) termination layer was reported to block the oxygen from approaching the active sites. The SrO is known as a large-band gap insulator and thus it is unlikely to enable electron transmission in ORR.…”
Section: Orr On Miec Cathodessupporting
confidence: 89%
“…Unfortunately, according to several research, LSCF electrodes made using conventional ceramic processes are terminated by Sr segregation, which has a considerable negative impact on ORR dynamics 4,25,50 . At high operating temperature, due to the strontium segregation, heterogeneous cation reactions in the LSCF materials suppressed the material stability.…”
Section: Orr On Miec Cathodesmentioning
confidence: 99%
See 2 more Smart Citations
“…The solid oxide fuel cell (SOFC) could efficiently convert chemical energy into electricity while emitting little pollution, making it a viable technology for addressing the present environmental issue [1]. Although conventional SOFCs with oxygenconducting electrolytes are commercially employed, the high working temperatures of traditional SOFCs (over 800°C) cause a number of issues, including reduced cell lifespan, challenges in selecting appropriate materials, and interlayer diffusions [2,3]. As a result, developing SOFCs that operate at lower temperatures (such as 700°C) is extremely desirable [4,5].…”
Section: Introductionmentioning
confidence: 99%